The Menganalisis Makna Simbolik Baju Adat Pesa’an Madura Jawa Timur - Sandy Al Fauzan, Muhammad Hafizh; Abrar, Fany Ramadhanty; Listiana, Indah; Hafbi, Najwa; Bahar, Syairul; Alfarauq, Farkhan Abdurochim (Program Studi Pendidikan Seni Rupa FBS UNJ, 2025)
Madurese traditional clothing is a rich cultural heritage from the island of Madura, Indonesia, which not only reflects the identity of the community, but also the social and cultural values ​​passed down from generation to generation. These clothes, which are generally made from brightly colored fabrics with unique motifs, play an important role in various traditional events and cultural celebrations. This research aims to explore the history, social meaning and development of pesana clothes in a modern context. The research method uses a qualitative approach with observation techniques, semi-structured interviews, and documentation to analyze the symbolic meaning of this traditional clothing. The research results show that ordered clothes not only function as cultural identity, but also contain deep meaning related to the character of the Madurese people. Each design element, such as color and motif, has a certain symbolism that reflects boldness and simplicity. In addition, ordered clothes are often worn at formal events and reflect the social status of the wearer. The transformation of the pesana shirt in a social and economic context shows its adaptability while still maintaining traditional values. It is hoped that this research can encourage the younger generation to preserve the rich culture of Madura in the modern era.